Integrating procurement, prescription, and resistance data to strengthen antimicrobial stewardship: insights from a public health institution in India - Modgil, Vinay; Sahay, Sundeep; Mukherjee, Arunima; Banta, Rashi; Joshi, Neha; Surial, Rashmi; Thakur, Subhash; Mazumdar, Suvodeep; Roychowdhury, Sneha; Taneja, Neelam (Frontiers in Microbiology, 2025)
IntroductionSustained and sub-optimal antimicrobial use drives antimicrobial resistance (AMR), a major health systems challenge in low- and middle-income countries (LMICs) such as India. This study examined the relationship between institutional antimicrobial procurement and outpatient prescribing patterns, and how these influence resistance trends identified through antibiotic susceptibility testing (AST) in a public community hospital.MethodsData were collected from three sources: (i) procurement records (2018–2022), (ii) AST results from urine, pus, and stool samples (2023–2024), and (iii) outpatient prescriptions (2023–2024). Each dataset was analyzed individually and in an integrated framework to assess interrelationships between antimicrobial use and resistance.ResultsAmoxicillin-clavulanate, ciprofloxacin, and doxycycline were among the most procured drugs, with Escherichia coli (urine) resistance rates of 53%, 87%, and 39%, respectively. The most frequently prescribed antimicrobials were Amoxicillin-Clavulanate (24%), Cefixime (15%), and Azithromycin (11%); over 50% were broad-spectrum agents and over 90% belonged to the WHO AWaRe “Access” category. Correlation analysis revealed a weak positive association between procurement and sensitivity, indicating that higher procurement did not necessarily increase resistance.DiscussionThese findings demonstrate the feasibility of linking institutional datasets to identify inefficiencies in antimicrobial use and guide evidence-based stewardship interventions, including formulary revision, procurement alignment, and data-driven prescribing practices.